Fundamental Prerequisites of Operational Readiness, Activation, and Transition: Case Study of Istanbul Grand Airport - Aladag, Hande; Demirdogen, Gokhan; Isik, Zeynep (MDPI, 2023)
Operational readiness, activation, and Transition (ORAT) is a series of processes that aims to convert an airport into an efficient business and make the personnel, processes, operations, and systems work in full harmony with each other. This paper aimed to determine the importance level of the fundamental prerequisites of the ORAT process. To fulfil this aim, the ORAT activities were first determined within a comprehensive literature review, and a descriptive case study was presented for illustrating the effects and the relations between the ORAT activities. Finally, the Pythagorean fuzzy analytical hierarchy process (PFAHP) method was used. Management of airport systems, Preparation of ORAT management and tracking systems, and Providing process, and documentation requirements for operational transition of the facility were found out as the three prominent ORAT activities. The study contributes to the body of knowledge with an empirical investigation of which of up-front activities in the ORAT process should be primarily focused. Thus, operational and risk management strategies can be developed by considering the fundamental prerequisites of ORAT on a preferential basis by practitioners. Additionally, the results of this study will also be an informative resource for the prevention of failures that are frequently encountered in ORAT experiences.
Keywords: airport management; case study; facility management; Pythagorean fuzzy analytic hierarchy process (PFAHP); operational readiness, activation, and transition (ORAT); PYTHAGOREAN FUZZY AHP; MODEL; FRAMEWORK; Social Sciences - Other Topics